Methotrexate versus cyclophosphamide for remission maintenance in ANCA-associated vasculitis: A randomised trial. - Federica Maritati; Federico Alberici; Elena Oliva; Maria L Urban; Alessandra Palmisano; Francesca Santarsia; Simeone Andrulli; Laura Pavone; Alberto Pesci; Chiara Grasselli; Rosaria Santi; Bruno Tumiati; et al. (PLoS ONE, 2017)
The treatment of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is based on remission-induction and remission-maintenance. Methotrexate is a widely used immunosuppressant but only a few studies explored its role for maintenance in AAV. This trial investigated the efficacy and safety of methotrexate as maintenance therapy for AAV.In this single-centre, open-label, randomised trial we compared methotrexate and cyclophosphamide for maintenance in AAV. We enrolled patients with granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA), the latter with poor-prognosis factors and/or peripheral neuropathy. Remission was induced with cyclophosphamide. At remission, the patients were randomised to receive methotrexate or to continue with cyclophosphamide for 12 months; after treatment, they were followed for another 12 months. The primary end-point was relapse; secondary end-points included renal outcomes and treatment-related toxicity.Of the 94 enrolled patients, 23 were excluded during remission-induction or did not achieve remission; the remaining 71 were randomised to cyclophosphamide (n = 33) or methotrexate (n = 38). Relapse frequencies at months 12 and 24 after randomisation were not different between the two groups (p = 1.00 and 1.00). Relapse-free survival was also comparable (log-rank test p = 0.99). No differences in relapses were detected between the two treatments when GPA+MPA and EGPA were analysed separately. There were no differences in eGFR at months 12 and 24; proteinuria declined significantly (from diagnosis to month 24) only in the cyclophosphamide group (p = 0.0007). No significant differences in adverse event frequencies were observed.MTX may be effective and safe for remission-maintenance in AAV.clinicaltrials.gov NCT00751517.